Optimization of Tire Production Planning Using The Goal Programming Method and Sensitivity Analysis - Vera Devani; Muhammad Isnaini Hadiyul Umam; Yulia Aiza; Sarbaini Sarbaini ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2022)
In Indonesia there are many companies that are engaged in tire retreading or reuse of unused used tires. One of the problems in the retread business in Indonesia is that the tire production target is often not fulfilled and the lack of available tires is used as the main raw material for retreading due to the long process of sending tires from consumers to companies. The purpose of this study is to determine the optimal needs of resources, determine the priority of achievement and determine the value of sensitivity to the optimum solution achieved. The method used in this study is the Goal Programming Method, because it is suitable for problems that have many goals because through its deviation, the method can automatically capture information about the relative achievement of the goals to be achieved. Based on the results of research that has been done, it can be concluded that the maximum income earned by the company is IDR 474,426,000 or an increase of 36% from the limit set by the company. In addition, it can also be concluded that the sensitivity range for the boundary quantity value is the distance at which the shadow price remains valid. If it increases above the upper limit of sensitivity (increases) or decreases below the lower limit (decreases), the value of the shadow price will change.